The Influence of Customer Experience on Customer Loyalty Through Repurchase Intention in Shopee Jakarta Users - Daffa Raffi Fadila; Mohamad Sajili (Journal of Applied Business Administration, 2025)
This research focuses on the Shopee platform to analyse the effect of customer experience on customer loyalty through repurchase intention as a mediating variable. A quantitative research design was employed, using purposive sampling to select respondents. A total of 131 participants took part in this study, comprising male and female residents of Jakarta aged 17 to 30 years who had made at least one purchase on Shopee within the past six months. Data were gathered through an online questionnaire distributed via Google Forms, utilising a four-point Likert scale ranging from strongly disagree to strongly agree. The collected data were analysed using the Partial Least Squares (PLS) technique through the SmartPLS software version 4.1.1.5. The results confirm that customer experience has a positive impact on both repurchase intention and customer loyalty, with repurchase intention also serving as a significant mediating factor between the two variables.